A pragmatic checklist to identify pediatric ICU patients at risk for cardiac arrest or code bell activation. (February 2016) - Niles, Dana E.; Dewan, Maya; Zebuhr, Carleen; Wolfe, Heather; Bonafide, Christopher P.; Sutton, Robert M.; DiLiberto, Mary Ann; Boyle, Lori; Napolitano, Natalie; Morgan, Ryan W.; Stinson, Hannah; Leffelman, Jessica; et al.
Abstract: Background: In-hospital cardiac arrest is a rare event associated with significant morbidity and mortality. The ability to identify the ICU patients at risk for cardiac arrest could allow the clinical team to prepare staff and equipment in anticipation. Methods: This pilot study was completed at a large tertiary care pediatric intensive care unit to determine the feasibility of a simple checklist of clinical variables to predict deterioration. The daily checklist assessed patient risk for critical deterioration defined as cardiac arrest or code bell activation within 24 h of the checklist screen. The Phase I checklist was developed by expert consensus and evaluated to determine standard diagnostic test performance. A modified Phase II checklist was developed to prospectively test the feasibility and bedside provider "number needed to train". Results: For identifying patients requiring code bell activation, both checklists demonstrated a sensitivity of 100% with specificity of 76.0% during Phase I and 97.7% during Phase II. The positive likelihood ratio improved from 4.2 to 43.7. For identifying patients that had a cardiac arrest within 24 h, the Phase I and II checklists demonstrated a sensitivity of 100% with specificity again improving from 75.7% to 97.6%. There was an improved positive likelihood ratio from 4.1 in Phase I to 41.9 in Phase II, with improvement of "number needed to train" from 149 to 7.4 providers. Conclusions: A novel high-risk clinical indicators checklist is feasible and provides timely and accurate identification of the ICU patients at risk for cardiac arrest or code bell activation.